Whole grain intake of Australians estimated from a cross-sectional analysis of dietary intake data from the 2011–13 Australian Health Survey. Issue 12 (8th June 2017) - Galea, Leanne M; Beck, Eleanor J; Probst, Yasmine C; Cashman, Chris J
Abstract: Objective: The Australian Dietary Guidelines recommend Australians choose mostly whole-grain and/or high-fibre varieties within the grains (cereal) foods category, with other groups specifying a whole grain Daily Target Intake of 48 g for Australians aged 9 years or above. The USA and UK report estimates of whole grain intake that are low and declining, and no comprehensive studies on whole grain intake in the Australian population are available. The present study aimed to determine national estimates of whole grain intake, compared with current recommendations. Design: A recently updated whole grain database was applied to the most current population dietary intake data. Single 24 h dietary recall intake data were reviewed against age group, sex, relative to energy intake and whole grain recommendations. Setting: Australia. Subjects: Australians (2–85 years) participating in the 2011–13 Australian Health Survey ( n 12 153). Results: The median daily whole grain intake was 21 g for adults (19–85 years) and 17 g for children/adolescents (2–18 years), or 28 and 23 g/10 MJ per d, respectively. Approximately 30 % of children/adolescents consumed no whole grains on the day of the survey. Whole grain intake was lowest for the age group 14–18 years (8·7 g/d). Of all participants aged ≥9 years, 73 % did not reach the recommended Daily Target Intake of 48 g. Conclusions: Whole grain intake in Australia is below recommendations in all age groups. Adolescents may be a key target for campaigns to increase whole grain consumption. This study provides the first quantification of absolute whole grain intake from all food sources in a national sample of Australians.